Development of uncut crop edge detection system based on laser rangefinder for combine harvesters - Teng, Zhao; Noguchi, Noboru; Liangliang, Yang; Ishii, Kazunobu; Jun, Chen (International Journal of Agricultural and Biological Engineering, 2016)
The objective of this research was to develop an uncut crop edge detection system for a combine harvester. A laser rangefinder (LF) was selected as a primary sensor, combined with a pan-tilt unit (PTU) and an inertial measurement unit (IMU). Three-dimensional field information can be obtained when the PTU rotates the laser rangefinder in the vertical plane. A field profile was modeled by analyzing range data. Otsu’s method was used to detect the crop edge position on each scanning profile, and the least squares method was applied to fit the uncut crop edge. Fundamental performance of the system was first evaluated under laboratory conditions. Then, validation experiments were conducted under both static and dynamic conditions in a wheat field during harvesting season. To verify the error of the detection system, the real position of the edge was measured by GPS for accuracy evaluation. The results showed an average lateral error of ±12 cm, with a Root-Mean-Square Error (RMSE) of 3.01 cm for the static test, and an average lateral error of ±25 cm, with an RMSE of 10.15 cm for the dynamic test. The proposed laser rangefinder-based uncut crop edge detection system exhibited a satisfactory performance for edge detection under different conditions in the field, and can provide reliable information for further study. Keywords: laser rangefinder technology, crop edge detection, combine harvester, navigation, field profile modeling DOI: 10.3965/j.ijabe.20160902.1959 Citation: Zhao T, Noguchi N, Yang L L, Ishii K, Chen J. Development of uncut crop edge detection system based on laser rangefinder for combine harvesters. Int J Agric & Biol Eng, 2016; 9(2): 21－28.